STUDENTS’ METACOGNITIVE STRATEGIES IN MASTERING WRITING EXPOSITION TEXT - Merryta Lestari (Journal of English Education Program (JEEP), 2017)
This study examines the effectiveness of students’ metacognitive strategies in improving students' skills in writing exposition text.The main problems of this study are: “what metacognitive strategies are used by the students in mastering writing exposition text?andwhich metacognitive strategies are dominantly used by students in mastering writing exposition text?.” The purposes of this study are to find out what metacognitive strategies are used by the students in mastering writing exposition text and to find out which metacognitive strategies are dominantly used by students in mastering writing exposition text.  The present study employs a case study method.The population in this study was all the eleventh grade of SMAN 1 Baregbeg in the academic year 2013/2014consisting of 4 classes of 88 students.The study took one class as a sample of the research. The sample of the study was XI IPS 1 consisting of 25 students.The instruments used to collect data were writing test and questionnaire. The result of this study revealed that the students like using metacognitive strategies in learning English. Based on the collected data it can be drawn that it is indicated by the students’ score of metacognitive strategies. Based on the conclusion, this study suggests that the use ofstudents’ metacognitive strategies in writing exposition textshould be implemented during teaching and learning process in class in order that the students can learn it step by step until they understand how to write exposition text.The present study suggests that the use of students’ metacognitive strategies in learning writing exposition text should be given to students during teaching and learning English writing. Keywords: Metacognitive strategies, writing exposition text.